Invalidation of the Transcriptional Modulator of Lipid Metabolism PPARβ/δ in T Cells Prevents Age-Related Alteration of Body Composition and Loss of Endurance Capacity - Rousseau, Anne-Sophie; Murdaca, Joseph; Le Menn, Gwenaëlle; Sibille, Brigitte; Wahli, Walter; Le Garf, Sébastien; Chinetti, Giulia; Neels, Jaap G.; Mothe-Satney, Isabelle (Frontiers in Physiology, 2021)
Anti-inflammatory regulatory T cells (Tregs) are the most metabolically flexible CD4+ T cells by using both glycolysis and Fatty Acid Oxidation (FAO) which allow them to migrate in tissues. With aging, Tregs accumulate in secondary lymphoid organs and are involved in impairment of skeletal muscle (SKM) regeneration and mass maintenance. In this study, we showed that a deletion of a FAO modulator, Peroxisome Proliferator-Activated Receptor beta/delta (PPARβ/δ), specifically in T cells (KO-T PPARβ/δ), increased the number of CD4+T cells at day 2 following a cardiotoxin-induced SKM regeneration. Older KO-T PPARβ/δ mice maintained a Tregs prevalence in lymph nodes similar to young mice. Surprisingly, KO-T PPARβ/δ mice were protected from the effects of age on lean and fat mass and endurance capacity. Our results lead us to propose an original potential role of T cell metabolism in the effects of aging on the maintenance of body composition and aerobic capacities.